Phytoconstituents profiling and antioxidant potential of Wrightia tinctoria R. Br. - Rajkumar, S.; Sathyaprabha, G.; Mathanmohun, Maghimaa (Current Botany, 2023)
In the Indian traditional system of medicine, Wrightia tinctoria R.Br. (Apocyanaceae) is recognized as a biologically effective therapeutic plant for the treatment of jaundice. It is a natural medicinal tree possessing antidiabetic, anti-inflammatory, hepatoprotective, antinociceptive, antifungal, antibacterial, antipsoriatic, antiviral, anthelmintic, anticancerous, analgesic, antipyretic, and aphrodisiac activities. Methanolic extract of W. tinctoria plant was investigated with Gas Chromatography–Mass Spectrometry (GC-MS), Fourier transform infrared spectroscopy (FTIR) and the antioxidant activity of W. tinctoria was analysed by most probable hydrogen peroxide scavenging (H2O2) activity, DPPH activity and Thiobarbutaric acid. The phytochemical in W. tinctoria leaf and bark have been assessed by GC-MS analysis. GC-MS analysis of W. tinctoria methanolic extract exposed the existence of the GC-MS chromatograms of 10 peaks in the leaf and 20 peaks in the bark. The FTIR spectroscopy analyses were identified by various functional compounds in the extracts with distinctive peak values. The FTIR analysis of methanolic leaf extracts of W. tinctoria confirmed the presence of alcohol, amine, alkane, carboxylic acid, sulfur compounds, halogen compounds and alkyne which showed major peaks. Also the methanolic bark extracts of W. tinctoria confirmed the presence of amines, phenol, alcohols, alkane, aldehydes, carboxylic acid, nitrogen compounds, sulfur compounds, and halogen compounds which also exhibited major peaks. Significant antioxidant activity is displayed by the plant part of leaf and bark sample. The results obtained in the determination of antioxidant activity of MEWT displayed considerable free radical scavenging capacity against DPPH which generated free radicals. This study includes the identification of phytochemicals and antioxidant potential of methanolic and aqueous extract of W. tinctoria which assist in therapeutic claims about this species in the traditional medicinal plant system.